2011
DOI: 10.1186/1743-7075-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chromium histidinate on high fat diet induced obesity in rats

Abstract: BackgroundChromium (Cr) is an essential trace element that has garnered interest for use as a weight loss aid, but its molecular mechanism in obesity is not clear. In this study, an attempt has been made to investigate the effects of chromium histidinate (CrHis) on glucose transporter-2 (GLUT-2), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), nuclear factor-kappa B (NF-κB p65) and the oxidative stress marker 4-hydroxynonenal adducts (HNE) expressions in liver of rats fed high fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 47 publications
9
37
0
1
Order By: Relevance
“…Chromium was found to normalize the values of K m and V max to near control levels. Chromium supplementation has been reported to induce GLUT2 activity [81] as well as to improve glucose disposal rates and significantly increase insulin-stimulated phosphorylation of IRS-1 and PI3-K activity in skeletal muscles of insulin-resistant JCR:LAcorpulent rat [82]. Wang and Yao [83] reported that the enhancing effect of CrP on glucose uptake in adipocytes involves the activation of p38MAPK.…”
Section: Discussionmentioning
confidence: 97%
“…Chromium was found to normalize the values of K m and V max to near control levels. Chromium supplementation has been reported to induce GLUT2 activity [81] as well as to improve glucose disposal rates and significantly increase insulin-stimulated phosphorylation of IRS-1 and PI3-K activity in skeletal muscles of insulin-resistant JCR:LAcorpulent rat [82]. Wang and Yao [83] reported that the enhancing effect of CrP on glucose uptake in adipocytes involves the activation of p38MAPK.…”
Section: Discussionmentioning
confidence: 97%
“…Despite no changes in expressions of hepatic NF-kB and IkB under the TN condition, increasing supplemental CrHis level decreased hepatic NF-kB expression and increased hepatic IkB expression in a dose-response manner under the HS condition. These nuclear factors are needed for activation (Nelson et al, 2004;Gilmore, 2006) and translocation Tuzcu et al, 2011), respectively, to overcome oxidative stress through inducing antioxidant defence system enzymes and detoxifying produced singlet oxygen and free radicals.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous work, we demonstrated that Cr-picolinate (CrPic; 1200 mg/kg) and Cr-chloride (CrCl 3 ) improved performance variables and suppressed lipid peroxidation and release of proinflammatory markers at a similar extent in quail reared under both thermoneutral (TN) and HS conditions (Sahin et al, 2010a). As a novel Cr chelate, Cr-histidinate (CrHis) was also shown to improve glucose metabolism in diabetic rats (Dogukan et al, 2009;Tuzcu et al, 2011). In terms of absorbability of Cr, it was greatest when it was chelated with histidine (Anderson et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Various natural and synthetic substances with the ability to stimulate Nrf2 have been verified to exert anti-obesity activity, including 1-[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole (CDDO-Im) [371], oleanolic acid [372,373], oltipraz [374], ellagic acid [375], quercetin [376], curcumin [377], resveratrol [378],and chromiumhistidinate [379]. Keap1 KD mice with a constitutive increase in Nrf2 activity have lower body weight and epididymal fat masse than WT mice [380].…”
Section: Nrf2 and Adipocyte Differentiationmentioning
confidence: 99%